Term Structure Modeling Using Exponential Splines: Discussion - Jordan, J. V. (Journal of Finance, 1982)
J. V. Jordan, Term Structure Modeling Using Exponential Splines: Discussion, The Journal of Finance, Vol. 37, No. 2, Papers and Proceedings of the Fortieth Annual Meeting of the American Finance Association, Washington, D.C., December 28-30, 1981 (May, 1982), pp. 354-356